Analysis of Natural Rutile (TiO2) by Laser-assisted Atom Probe Tomography - Verberne, R.; Saxey, David; Reddy, Steven; Rickard, William; Fougerouse, Denis; Clark, Christopher (Cambridge University Press, 2019)
Since the introduction of laser-assisted atom probe, analysis of nonconductive materials by atom probe tomography (APT) has become more routine. To obtain high-quality data, a number of acquisition variables needs to be optimized for the material of interest, and for the specific question being addressed. Here, the rutile (TiO2) reference material 'Windmill Hill Quartzite,' used for secondary ion mass spectrometry U-Pb dating and laser-ablation inductively coupled plasma mass spectrometry, was analyzed by laser-assisted APT to constrain optimal running conditions. Changes in acquisition parameters such as laser energy and detection rate are evaluated in terms of their effect on background noise, ionization state, hit-multiplicity, and thermal tails. Higher laser energy results in the formation of more complex molecular ions and affects the ionization charge state. At lower energies, background noise and hit-multiplicity increase, but thermal tails shorten. There are also correlations between the acquisition voltage and several of these metrics, which remain to be fully understood. The results observed when varying the acquisition parameters will be discussed in detail in the context of utilizing APT analysis of rutile within geology.